Sensibilidad y motricidad oral (Ediciones UC, 2018)
Sensitivity and oral motor skills includes the knowledge to understand the vital function that the oral cavity fulfills in the human being and that it is mainly carried out autonomously. The reader will find a systematic description of contents related to the neurophysiological bases involved in sensitivity and oral motor skills, in such a way that it serves as a guide for learning in the various health careers that require their study. Step by step, the nervous pathways involved in the motor and sensory control of the oral cavity are described, the different reflex arcs involved in oral physiology are exposed, the motor control of posture and the voluntary activity of the functions that oral cavity executes and explains the ontogenic development of some motor oral functions. In short, a book that is key due to its timeliness and clarity in the study of doctors, dentists and related careers.